2003
DOI: 10.1200/jco.2003.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neurological Outcome of Childhood Brain Tumors Treated by Surgery Only

Abstract: In patients who received operation as the only treatment for their brain tumor, there was a good chance of total or partial recovery of preoperative and postoperative neurological deficits, although only one third of the patients will have no long-term neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 28 publications
2
52
0
2
Order By: Relevance
“…17 Sønderkaer et al reported 69% of patients with brain tumors had a neurological deficit approximately 10 years from treatment, and using the Bloom's score, which closely mirrors aspects of the PCPC score, they estimated 23% had moderate disability and 2% had severe disability. 27 The similarities among cognitive outcomes were consistent despite variation in length of follow-up and measures of outcome (i.e., Bloom's score, intellectual quotient, and parent/patient questionnaire). 16 (12) 20 (20) 27 (42) 8 (62) 1 (100) 0 <0.001…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…17 Sønderkaer et al reported 69% of patients with brain tumors had a neurological deficit approximately 10 years from treatment, and using the Bloom's score, which closely mirrors aspects of the PCPC score, they estimated 23% had moderate disability and 2% had severe disability. 27 The similarities among cognitive outcomes were consistent despite variation in length of follow-up and measures of outcome (i.e., Bloom's score, intellectual quotient, and parent/patient questionnaire). 16 (12) 20 (20) 27 (42) 8 (62) 1 (100) 0 <0.001…”
Section: Discussionmentioning
confidence: 89%
“…1,7,17,21,22,27,32 Macedoni-Luksic et al reported 62% of children with brain tumors had at least 1 neurological impairment, with 22% moderately disabled and 2% severely disabled more than 3 years after treatment. 17 Sønderkaer et al reported 69% of patients with brain tumors had a neurological deficit approximately 10 years from treatment, and using the Bloom's score, which closely mirrors aspects of the PCPC score, they estimated 23% had moderate disability and 2% had severe disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As children who survive brain tumours face the risk of late neurocognitive deficits 10, 11, 12, as well as endocrine 4 and neurological 3 dysfunctions, the psychological burden on the children, parents and the whole family is great. The child's cognitive problems must also be recognised early and taken into consideration when planning the child's schooling 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…The three remaining studies [117,227,228] involved a high proportion of non-neoplastic lesions that were not analyzed distinctly from neoplastic cases. Mean seizure free rates across the three studies ranged from a low of 56% to a high of 81%, with seizure improvement noted in 81.3% and 92.4% in the two studies in which this outcome was reported [117,227].…”
Section: The Benefits and Risks Of Surgerymentioning
confidence: 99%